2017
DOI: 10.1016/j.ctcp.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Blurred lines: Emerging practice for registered dietitian-nutritionists in integrative and functional nutrition

Abstract: The orientation towards Integrative Medicine for a majority of US dietitians is in the awareness and learning phases of adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Admittedly, the effect size was small, but in a separate paper the authors demonstrated that integrative nutrition practice diffusion is in the early phase of adoption, but is more common within certain communities of practice. A separate paper described the characteristics and evidence-based professional certifications and licenses earned by dietitians in the specialization of integrative and functional medicine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Admittedly, the effect size was small, but in a separate paper the authors demonstrated that integrative nutrition practice diffusion is in the early phase of adoption, but is more common within certain communities of practice. A separate paper described the characteristics and evidence-based professional certifications and licenses earned by dietitians in the specialization of integrative and functional medicine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Satisfaction with Life scale (SWLS) was the outcome variable of interest measuring individual perceptions of the meaning of health [ 19 ]. Separate papers were devoted to the validation process of the English version of the Healthy Lifestyle and Personal Control Questionnaire (HLPCQ) and Integrative Medicine (IM-30) [ 20 , 21 ] The HLPCQ measures personal routines and the degree to which the individual is empowered through lifestyle and health choices [ 17 ]. The IM-30 measures professional practice patterns along a continuum from traditional to integrative styles of practice for physicians.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Grace-Farfaglia et al23 reported that RDs may be reluctant to incorporate IM-based therapies in their respective practices. They hypothesize that this may be due to a lack of: IM-based training during their didactic curricula, evidence regarding the efficacy of IM therapies, published evidence-based practice guidelines from the Academy, and how these IM modalities will fit into their overall treatment plan 23. This may partly explain the reported differences in IM use among practice areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although the dietetics syllabus has introduced related topics such as complementary and alternative medicine and wellness (19), dietitians are not trained to address their patients' spiritual care (13). If they were to practice, they might work it out based on their personal experiences and interest (20).…”
Section: Discussionmentioning
confidence: 99%
“…Many dietitians would now consider adopting new dietetics approaches such as mindfulness and spiritual well-being (22). In addition, there has been a growing interest to adopt integrative medicine orientation into medical nutrition therapy among dietitians in the United States (20). While research into technical issues in promoting a patient-centred approach in dietetics ( 23) is important, now it is high time for dietetic professionals to consider spiritual care in their practices.…”
Section: Discussionmentioning
confidence: 99%